Les conditions pour la représentation des fonctions par les séries d’interpolation - Nasekovskaja, N. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. С. Насековская. Условия представимости аналитических функций интерполяционными рядамиN. Nasekovskaja. Analizinės funkcijos interpoliacinėmis eilutėmis išreiškimo sąlygos